First communication on the efficacy of combined 177Lutetium-PSMA with immunotherapy outside prostate cancer. Issue 10 (26th October 2022) - Digklia, Antonia; Boughdad, Sarah; Homicsko, Krisztian; Dromain, Clarisse; Trimech, Mounir; Dolcan, Ana; Peters, Solange; Prior, John; Schaefer, Niklaus
Abstract : Prostate-specific membrane antigen (PSMA)-targeted radioligand therapy is a validated treatment option for patients with advanced prostate cancer. Although PSMA expression is not limited to prostate tissue, little is known about its relevance to other types of cancer. Here, we present a case report of a patient with uterine leiomyosarcoma that is progressing while on immunotherapy and treated with 177 Lu-PSMA radionuclide therapy. We report for the first time that 177 Lu-PSMA radionuclide therapy combined with immunotherapy outside of prostate cancer. We did observe post-treatment reduction of tumor growth rate, although we did not notice disease response based on RECIST criteria. We suggest that 177 Lu-PSMA treatment especially combined with immunotherapy may be an option for patients with cancer without other therapeutic options. Insights: 177 Lu-PSMA radionuclide therapy should be considered for any tumor stained positive for PSMA.